In-Hospital and Long-Term Prognosis after Myocardial Infarction in Patients with Prior Coronary Artery Bypass Surgery; 19-Year Experience. (2009) - Mitrovic, Predrag M.; Stefanovic, Branislav; Vasiljevic, Zorana; Radovanovic, Mina; Radovanovic, Nebojsa; Krljanac, Gordana; Novakovic, Ana; Ostojic, Miodrag
Abstract : To present a 19-year experience of the prognosis of patients with acute myocardial infarction (AMI) and prior coronary artery bypass surgery (CABS), 748 patients with AMI after prior CABS (postbypass group) and a control group of 1080 patients with AMI, but without prior CABS, were analyzed. All indexes of infarct size were lower in the postbypass group. There was more ventricular fibrillation in the postbypass group. In-hospital mortality was similar ( p = 0.3675). In the follow-up period, postbypass patients had more heart failure, recurrent CABS, reinfarction, and unstable angina than did control patients. Cumulative survival was better in the control group than in the postbypass group ( p = 0.0403). Multiple logistic regression model showed that previous angina ( p = 0.0005), diabetes ( p = 0.0058), and age ( p = 0.0102) were independent predictor factors for survival. Use of digitalis and diuretics, together with previous angina, also influenced survival ( p = 0.0092), as well as male gender, older patients, and diabetes together ( p = 0.0420). Patients with AMI after prior CABS had smaller infarct, but more reinfarction, reoperation, heart failure, and angina. Previous angina, diabetes, and age, independently, as well as use of digitalis and diuretics together with angina, and male gender, older patients, and diabetes together, influenced a worse survival rate in these patients.